Efficiency Improvement of Patch Antenna with Metamaterial Technique for Modern Wireless Communication Applications - P. Kamphikul (2020)
© 2019 IEEE. This paper is conducted to present the design and analysis of the antenna system for modern wireless communication to improve the efficiency of an access point for connecting the wireless network. A wideband patch array with a new technique of metamaterial on Electromagnetic Band Gap (EBG) structure is utilized to demonstrate the possibility of a high efficiency omnidirectional antenna. The patch array antenna that provides the wide bandwidth, covered frequency ranges for modern wireless communications following the IEEE80211 standard for WLAN (Wireless Local Area Network), the IEEE 80216 standard for WiMAX (Worldwide Interoperability for Microwave Access), and mobile GSM technologies. Besides, this antenna provides not only the moderately high gain, but also the omnidirectional pattern that is more appropriate for both indoors and outdoors such as the large buildings and the public parks, or for point-to-multipoint interfaces. Moreover, the method to enhance and develop the effectiveness of the antenna by transferring the electromagnetic fields from a patch array antenna radiated through the proper structure of EBG is reported in this paper. The appropriate EBG structure is a new technology for the improvement of the performances of an antenna in terms of gain, side and back lobe levels, and mutual coupling. Because, this EBG structure has the capability to open a bandgap, which is a frequency range for which the propagation of electromagnetic waves is forbidden. From the investigation, the proper structure of the EBG, which is the cavity of the cylindrical woodpile EBG structure that is more suitable for beam shape, as the additional resonant circuit covered a wideband patch array antenna. This proposed technique not only has the advantages of reducing the total length of the patch array, but also provides higher gain and low profile.